2022
DOI: 10.53730/ijhs.v6ns5.11400
|View full text |Cite
|
Sign up to set email alerts
|

immediate effect of induced muscular fatigue on static and dynamic balance and core strength in male volleyball players

Abstract: Introduction: Muscular fatigue causes impaired joint proprioception and postural control which can affect performance. Fatigue affects the capacity of the muscle to generate force which ultimately leads to injuries and diminish performance. The effect of fatigue on static and dynamic balance in volleyball players was inadequately known. Aim: To assess the effects of induced muscular fatigue on static and dynamic balance and core strength in volleyball players. Methodology:  Twenty male volleyball players were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It has been suggested that the vertical jump test has influence on the ability of subjects to use the elastic and neural benefits. [16] Hopping exercises has shown improvement in time to stabilization and the perception of instability in athletes with chronic ankle instability. [6] It is important to gain faster post-landing stability for prevention of the ankle injury.…”
Section: Balancementioning
confidence: 99%
“…It has been suggested that the vertical jump test has influence on the ability of subjects to use the elastic and neural benefits. [16] Hopping exercises has shown improvement in time to stabilization and the perception of instability in athletes with chronic ankle instability. [6] It is important to gain faster post-landing stability for prevention of the ankle injury.…”
Section: Balancementioning
confidence: 99%